Attitudes to and beliefs about animal assisted therapy for children with disabilities. (February 2017) - Yap, Esther; Scheinberg, Adam; Williams, Katrina
Abstract: Objectives: This study assessed the attitudes and beliefs surrounding animal-assisted therapy (AAT) for the rehabilitation of children with disabilities at the Royal Children's Hospital (RCH), focusing specifically on cerebral palsy (CP), autism spectrum disorder (ASD) and acquired brain injury (ABI). This was an initial step to inform future AAT research and to understand the feasibility of interventions. Design/Setting/Outcome measures: An online survey asking participants their opinions about the inclusion of AAT, and potential barriers to its introduction in a tertiary hospital setting was advertised on the RCH Intranet from 3 March 2015 to 3 April 2015. Results: A total of 128 participants responded to the survey request, from a range of specialties and departments. Almost all survey respondents reported that animal-assisted therapy would be helpful in the physical or behavioral management of children affected by CP (98%), ASD (99%) and ABI (96%), and 98% of survey respondents supported the inclusion of AAT in the RCH. Ninety-two percent recommended AAT in the inpatient setting and 52% of the respondents suggest that it should be administered as a pre-determined program with set activities. Additionally, qualitative responses provided suggestions that AAT should be used to provide comfort in high stress environments such as prior to medical and surgical procedures. Conclusions: The majority of staff are supportive of the inclusion of AAT in the RCH, indicating more research is needed to establish whether AAT is acceptable to children and families as part of their care.